Managing digital bridges: how online social capital translates digital literacy into higher education access - Wang, Shiwei; Alam, Gazi Mahabubul; Skrbinjek, Vesna; Bashir, Karima; Lei, Miao (SAGE Publications, 2025)
Background: In the modern computer-driven economy, digital technologies have reshaped the distribution of opportunities and tasks in higher education. Objective: Whether digital literacy and online social capital, as products of the digital age, serve as “equalizers” to promote equity by enabling individuals to improve their socioeconomic conditions/status, or function as “new barriers” that reinforce disparities due to the effects of established social stratification, is a core issue that needs to be explored. Methods: Using a quantitative research design with a sample of 384 high school graduates recruited from a province in western China, this study explores the mechanisms by which digital literacy and online social capital affect access to higher education through multivariate logistic regression and group regression comparative analysis. Results: The results reveal that digital literacy had a significant positive effect on access to higher education, and consequently this effect differed significantly by institution type and socioeconomic background. The study confirms that network social capital plays a mediating role between digital literacy and access to higher education. Conclusions: These findings provide: first, empirical evidence for understanding inequality in education in the digital age and second, important insights for the development of digital policies to promote educational equity.